2018
DOI: 10.4265/bio.23.207
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Staphylococcal Enterotoxin A Production and Growth of <i>Staphylococcus aureus</i> in Shaking and Stationary Cultures

Abstract: Staphylococcal food poisoning, which is still a serious health problem worldwide, is caused by staphylococcal enterotoxin SE. Among many types of SE, staphylococcal enterotoxin type A SEA is known to be the most responsible for staphylococcal food poisoning. Production by SEA-producing strains in shaking culture has been studied by many investigators, whereas the kinetical differences between shaking and stationary cultures have not been studied intensively. Therefore, this difference was studied at various te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…It is known that the toxin production varies among S. aureus strains and the toxin type (Czop & Bergdoll, ; Otero, Garcia, Garcia, Moreno, & Bergdoll, ). The varieties of SEA production and cell growth of the five strains in the present study were also observed in shaking culture (Elahi et al., ).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…It is known that the toxin production varies among S. aureus strains and the toxin type (Czop & Bergdoll, ; Otero, Garcia, Garcia, Moreno, & Bergdoll, ). The varieties of SEA production and cell growth of the five strains in the present study were also observed in shaking culture (Elahi et al., ).…”
Section: Resultssupporting
confidence: 78%
“…. varieties of SEA production and cell growth of the five strains in the present study were also observed in shaking culture (Elahi et al, 2018). When the maximum SEA and cell concentrations in the cocktail were compared to those of the individual strains, these values in the cocktail were higher than the averages of the five strains under the same conditions.…”
Section: Food Microbiology and Safetysupporting
confidence: 53%
See 3 more Smart Citations